Semiotic Identity Construction of VTuber Storytelling in YouTube Shorts: Konstruksi Identitas Semiotik dari Penceritaan VTuber di YouTube Shorts - Aliyah Nanda Alfita; Istiqomah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The growth of short video platforms has accelerated the development of digital content formats, including VTuber performances that combine animation technology, storytelling, and convergent media communication. Specific Background: VTubers use Live2D avatars and narrative content to present visual communication integrating gaming, Japanese mythology, and anime aesthetics through YouTube Shorts. Knowledge Gap: Previous studies mainly discuss VTubers in general visual communication, while limited research analyzes symbolic meaning construction in short video storytelling using semiotic approaches. Aims: This study analyzes how visual and symbolic signs construct identity and meaning in VTuber Yatagarasu no Yuta using Roland Barthes’ semiotic framework. Results: The findings show that avatar visual elements such as crow attributes and formal clothing represent literal meaning, while Minecraft creepypasta storytelling reflects symbolic themes of mystery, isolation, and digital threats. Mythological elements through characters like Herobrine, Entity 303, and Null represent digital urban legends reflecting collective fears in virtual environments. Novelty: This research integrates semiotic analysis with VTuber short video storytelling to explain layered signification in convergent media. Implications: The findings provide insights into VTuber identity formation, digital myth construction, and audience interaction patterns within virtual entertainment and digital culture studies. Highlights: Multi-Layered Sign Interpretation Reveals Symbolic Representation Within Gaming Narrative Elements. Short-Form Narrative Content Constructs Cultural Meaning in Virtual Community Interactions. Digital Legends Derived From Creepypasta Strengthen Virtual Persona Authenticity. Keywords: Vtuber Identity, Semiotic Analysis, YouTube Shorts, Digital Storytelling, Roland Barthes